The Importance of Family Relations for Cannabis Users: The Case of Serbian Adolescents - Zorica Terzic Supic; Milena Santric Milicevic; Isidora Sbutega; Vladimir Vasic (Tehran University of Medical Sciences, 2013)
Background: Adolescence is transitional stage of physical and mental human development occuring between childhood and adult life. Social interactions and environmental factors together are important predictors of adolescent cannabis use. This study aimed to examine the relationship between the social determinants and adolescents behavior with cannabis consumption.Methods: A cross sectional study as part of the European School Survey Project on Alcohol and other Drugs was conducted among 6.150 adolescents aged 16 years in three regions of Serbia, and three types of schools (gymnasium, vocational - professional, and vocational - handicraft) during May - June 2008. A multivariate logistic regression analysis was carried out to obtain adjusted odds ratios with 95% conﬁdence intervals in which the dependent variable was cannabis consumption non-user and user.Results: Among 6.7% of adolescents who had tried cannabis at least one in their lives, boys were more involved in cannabis use than girls, especially boys from gymnasium school. Well off family, lower education of mother, worse relations with parents were significantly associated with cannabis use (P < 0.05). Behaviors like skipping from schools, frequent evening outs, and playing on slot machines were also related to cannabis use (P < 0.05).Conclusions: The study confirmed the importance of family relationship development. Drug use preventive programmes should include building interpersonal trust in a family lifecycle and school culture.